PROSPEK PENGEMBANGAN KOMODITI JAGUNG MELALUI PENDEKATAN AGRIBISNIS DI KECAMATAN KULO, KABUPATEN SIDENRENG RAPPANG - Muhammad Natsir; Rikawanto Eko Mulyawan (Universitas Tribhuwana Tunggadewi, 2008)
This study was aimed to elucidate trend of harvesting area and maize yield, and policies supporting maize delopment through agribusiness approache in Kulo District of Sidenreng Rappang Regency. This study was conducted at Kulo District which is are known as a maize development area in Sidenreng Rappang Samples selected for this study comprised 50 farmers of 310 maize farmers at Kulo District. The collected data were then subjected to Qualitative-descriptive, trend and SWOT analyses. Results of this study showed that: (1) trends of harvest area and production of maize were linear and tended to increase every year, and (2) the policy strategies adopted for maize development using agribusiness approach were (a) production aspect, (b) institutional aspect, (c) financial aspects, (d).Harvest technology aspect, and (f) human resource aspects